Personal Adjustment and Disruptive Behaviors in Primary School Students - Martínez-Vicente, Marta (2020)
Objective. This study analyses the relationships between personal adjustment and disruptive behaviors in a group of 136 primary school students between the ages of 9 and 12. Method. This field observation study used a non-experimental, cross-sectional methodology. Several questionnaires were used to measure students’ selfesteem, personality, stress, and emotional competencies. Moreover, an ad hoc questionnaire was created to record disruptive behaviors. Results. The results indicate significant positive relationships between disruptive behaviors and school stress, as well as negative ones with self-esteem, stability, competence, and emotional understanding. The differences are significant according to gender, with inappropriate behaviors manifesting to a lesser extent in the case of girls.